Into the deep blue sea: Commons theory and international governance of Atlantic Bluefin Tuna. Issue 2 (August 2014) - Epstein, Graham; Nenadovic, Mateja; Boustany, André
The need to understand how to sustainably govern oceanic fisheries has become increasingly urgent as their contribution to global food security and livelihoods are threatened by declining stocks. Atlantic Bluefin Tuna (ABFT) is a prominent example of the complexities associated with widely distributed oceanic resources, extending in this case to include much of the North-Atlantic and Mediterranean Sea. This distribution has led to limited attention from commons theorists that tend to focus on small-scale social ecological systems. Therefore in order to explore the fit between theories of the commons developed in small-scale systems, we apply the Social-Ecological Systems Meta-Analysis Database (SESMAD) to systematically analyze ABFT governance over a 22 year period. The results, which focus on the effects of resource characteristics, broadly correspond to the expectations of commons theory. Interestingly, however, the addition of resource storage in the form of ABFT ranches appears to be contributing to unsustainable harvests. This stands in contrast to previous findings in the commons literature that storage tends to enhance prospects for sustainable governance. Therefore several alternative hypotheses are developed by comparing and contrasting attributes of ABFT and canal irrigation storage. These hypotheses may be used in future research to evaluate the conditions in which storage enhances prospects for sustainable governance.